Follow the money : how foundation dollars change public school politics - Reckhow, Sarah (New York : Oxford University Press, 2013)
In this work, Sarah Reckhow shows where and how foundation investment in education is occurring and presents in-depth analysis of the effects of these investments within the two largest urban districts in the United States: New York City and Los Angeles.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Keywords: Public schools -- United States -- Finance; Privatization in education -- United States